PENGGUNAAN MEDIA SOSIAL DALAM MEMOTIVASI BELAJAR MAHASISWA PPKN FKIP ULM: PERSPEKTIF KEWARGANEGARAAN DIGITAL - Salamah, Umi; Sarbaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the use of Sharing and Relationship functions on social media by students in the Pancasila and Civic Education (PPKn) program to motivate learning from a digital citizenship perspective. The main issue addressed in this study stems from the distraction caused by entertainment content, which hinders students’ ability to focus on their studies amid their high levels of academic activity on social media. The objective of this study is to analyze the behavior, role, and impact of Sharing and Relationships on students’ learning motivation. The research method employed is descriptive qualitative, utilizing data collection techniques such as observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The research findings indicate that: (1) Sharing and Relationship-building behaviors for academic purposes have been effective through the use of WhatsApp, Instagram, YouTube, and Tiktok; (2) these functions play a crucial role in motivating learning by fulfilling the needs for relatedness, a sense of security, and social learning; (3) positive impacts are evident in digital citizenship maturity, which involves the application of ethics, literacy, and responsibility, although the challenge of information distraction remains. In conclusion, students have actively utilized Sharing and Relationship functions to support academic performance and learning motivation; however, they still require strengthened self-regulation regarding digital distractions. It is recommended that students continue to enhance their digital literacy to maintain the effectiveness of responsible learning on social media.